Confirmation of Endoparasites Medication Result of Diarrhoea on Long Tailed Macaque (Macaca fascicularis) in Captivity (Indonesian Journal of Primatology, 2026)
Health problems in captive Macaca fascicularis populations still occur frequently, one of which is a disease caused by endoparasites, particularly worms. Anthelmintic treatment plays an essential role in controlling worm infestations. Thus, this study was conducted to confirm the effectiveness of anthelmintic (ivermectin) treatment in controlling gastrointestinal worm infestations caused by diarrhea in the M. fascicularis breeding colony. This descriptive study focused on identifying worm eggs in monkey feces using the formalin-acetate concentration technique. The results showed that only two samples (4%)  contained worms, and two species of eggs were identified, namely Strongyloides sp. (2%) and Trichuris sp. (2%). Worms did not cause diarrhea; enteropathogenic bacteria from food, water, and the environment around the monkey cage probably caused it. Therefore, it is essential to implement preventive measures to prevent diarrhea. The administration of ivermectin is effective in controlling gastrointestinal worms that cause diarrhea.